2000
DOI: 10.1029/1999gl003688
|View full text |Cite
|
Sign up to set email alerts
|

Field‐aligned currents generated in magnetotail reconnection: 3D Hall‐MHD simulations

Abstract: Understanding the field aligned current (FAC) system in substorms is one of the central themes of magnetospheric physics. Three‐dimensional (3D) magnetohydrodynamic (MHD) simulations of magnetotail reconnection has shown that FAC structures similar to the wedge‐current system are indeed reproduced either with or without a dipolar region situated at the earthward end of a current sheet. In this study, however, by noting that the ion inertia length is not negligibly small compared to the current sheet width in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 11 publications
5
29
0
Order By: Relevance
“…Hence, the FACs of the Hall current circuit form a thin double-sheet structure near the separatrix layer. Hall-MHD simulations showed that such smallscale currents can be seen even away from the reconnection site (Yamade et al, 2000).…”
Section: Phenomena Occurring In the Vicinity Of The Nightside Polar Cmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, the FACs of the Hall current circuit form a thin double-sheet structure near the separatrix layer. Hall-MHD simulations showed that such smallscale currents can be seen even away from the reconnection site (Yamade et al, 2000).…”
Section: Phenomena Occurring In the Vicinity Of The Nightside Polar Cmentioning
confidence: 97%
“…At the boundary, Alfvén waves carried a FAC pair with upward FAC on the equatorward and downward FAC on the poleward side. Yamade et al (2000) estimated from their simulation that the current densities at the ionospheric level would be 5 µA/m 2 .…”
Section: Phenomena Occurring In the Vicinity Of The Nightside Polar Cmentioning
confidence: 99%
“…According to Lockwood (1997) the open-closed boundary can be identified from the diffuse electron precipitation from the plasma sheet boundary layer or from the equatorward drifting arcs which form just equatorward of the open-closed boundary Hoffman et al, 1994) and are embedded in this diffuse precipitation. These arcs are also associated with intense electric fields (Pedersen et al, 1985) and thought to be Alfvén wave signatures of processes near or at the reconnection line (Hesse et al, 1999;Yamade et al, 2000). The accuracy by which one can determine the open-closed boundary is therefore highly dependent on the sensitivity and spatial resolution of the instruments that are used.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the Hall term to produce an additional current system in the proximity of the reconnection site has been known for a long time from a theoretical point of view (e.g., Sonnerup, 1979;Terasawa, 1983;Mandt et al, 1994;Hesse and Winske, 1994;Lottermoser et al, 1998;, and has been recently reported to be observed in the magnetotail (Oieroset et al, in preparation;Nagai et al, 1998). In order to see if this effect will modify the global FAC pattern, we have run a series of 2D Hall-MHD simulations to find that this additional current system can indeed be significant globally (Yamade et al, 2000). 2D simulations are started from the same initial condition as described above except that R y = ∞.…”
Section: Study On the Earth's Casementioning
confidence: 98%